Understanding the role of the dealers and the distribution channel for passenger cars in the automotive industry in Europe and India - Gupta, Shivi (2008)
In the automotive industry, the dealer plays a very important role in the distribution channel and is the 'face' with which the customer identifies and through whom he experiences the brand i.e. the car itself. Until recently, not much has been studied about the dealers and their role in the distribution channel while significant research has been done for the upstream supply chain management in the automotive industry. This study thus aims to provide a better understanding about the role of the dealer with a focus on the passenger car segment. In order to do this, the distribution channel has been studied along with the evolution of the channel and how this has had an impact upon the dealer's role. This has been done for the major markets in Europe (France, Germany, Italy and the UK) as well as for India. Many differences emerged between the European and the Indian markets like the emergence of large dealer groups in Europe that have been growing rapidly on the one hand and the dealerships in India that are still run as family businesses on the other hand. There has been an attempt to suggest improvements for the Indian market as learnt from European markets. The dealer-manufacturer relationships have also been studied which highlight certain issues that the dealers are currently facing with the manufacturers and there are suggestions to improve these like the use of a Dealer Satisfaction Index (DSI) for measuring dealer satisfaction and attempting to enhance it. The role of the internet has also been covered to see how this has affected the distribution channel and what role it might play in the future. Based on the analysis, findings and discussion, study comes up with recommendations for the dealers, manufacturers as well as for certain changes in the market structure where needed with a view to improve the overall effectiveness of the distribution channel.